2014
DOI: 10.5782/2223-2621.2014.17.1.70
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Shifts in English Translations of The Quran: A Case Study on “Yusuf” Chapter

Abstract: Long since Translation Studies emerged as a nascent academic discipline, it has seen a considerable number of descriptive theories and models, among which, Catford’s (1965) translation ‘shift’ approach has garnered particular attention within the realm of translational comparative studies. Quranic texts have constantly been the center of attention, as the Quran has established itself as the most famous and sublime text in Arabic. As such, the present comparative study aimed at investigating the frequencies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When the findings of this research were compared to another relevant research finding as in Dewi (2016), Dorri (2016), andMobarakeh (2016), it was found that the dominant shift occurred was structure shift which was similar to the finding of this research. While in Rezvani (2014), Herman (2014 and Maasoum (2013) found that the dominant shift occurred was unit shift. The difference occurred because of the linguistics characteristics and features to convey a message, it has its own system and form.…”
Section: Discussionmentioning
confidence: 99%
“…When the findings of this research were compared to another relevant research finding as in Dewi (2016), Dorri (2016), andMobarakeh (2016), it was found that the dominant shift occurred was structure shift which was similar to the finding of this research. While in Rezvani (2014), Herman (2014 and Maasoum (2013) found that the dominant shift occurred was unit shift. The difference occurred because of the linguistics characteristics and features to convey a message, it has its own system and form.…”
Section: Discussionmentioning
confidence: 99%
“…5 The Quranic verse "We have certainly honoured the children of Adam" can be read as explicit recognition of human dignity. 6 This passage emphasises that every person has inherent value, regardless of race, gender or social standing. 7 The Islamic view of human dignity derives from the conviction that all people are formed in God's image and equipped with special abilities that distinguish them from other living things, such as reason and free will 8 .…”
Section: Human Dignity In Islamic Thoughtmentioning
confidence: 99%
“…17 From the perspective of personal dimension, Islam's idea of human dignity at the level of the individual is based on the belief that each person is unique and created by God with qualities like reason and free will that make them different from other things. 18 This intrinsic value is a quality that all people possess that transcends a person's race, gender, social standing or any other distinguishing qualities. 19 The social concern aspect of human dignity is reflected in the guiding principles of social justice, equality and compassion in Islamic ethics.…”
Section: Human Dignity In Islamic Thoughtmentioning
confidence: 99%
“…The notion of Translation shifts was also investigated in Islamic texts. Rezvani and Nouraey (2014)conducted a comparative analysis study adopting Catford model of analysis where they specifically analyzed the occurrence of translation shifts in the English translation of the Holy Quran. The researchers selected seven translations of the first thirty verses of the chapter of 'Yousif'.…”
Section: Previous Studiesmentioning
confidence: 99%